Prospek industri penerbitan di Kabupaten Rejang Lebong: Studi pada penerbit CV Andhra Grafika - Rodin, Rhoni; Anjelika, Vera; Wilawati, Widiya; Ninsik, Wyli Fitri (Daluang: Journal of Library and Information Science, 2024)
Purpose. This study aims to analyze the prospects for the publishing industry in Rejang Lebong district, by taking the research location at Andhra Graphic publishers.Methodology. This study used descriptive qualitative method. Data collection is done by observation, interviews, and documentation.Results and discussion. The results show that the prospects for publishing businesses in Indonesia may vary depending on various factors, including industry trends, technological developments, government policies, and consumer preferences. It is important to note that in any industry, including publishing, there are risks and opportunities. Doing careful market research, understanding your target audience and having a solid business strategy will help you take the right steps to grow your publishing business. The prospect of a publishing business like Andhra Graphica in Rejang Lebong Regency has exciting potential, especially given your focus on more localized publishing services and accessibility to education and local culture. There are several ways that the Andhra Graphic publishing business can develop and contribute positively to Rejang Lebong Regency, including: 1) Local curriculum development; 2) Literacy and interest in reading; 3) Publishing local works; 4) Cultural and historical publishing; 5) Partnership with schools and educational institutions; 6) Technology-based publishing; 7) Efficient local distribution; 8) Promotion of culture and education; and 9) Community involvement.Conclusions. The regional publishing industry has very good prospects. Moreover, if the area does not yet have a publisher or there are still very few publishers. One example is Andhra Graphic Publisher, even though it is located in remote areas in Rejang Lebong.